Post-liver transplantation recurrence of primary sclerosing cholangitis: role of autologous hematopoietic stem cell transplantation. (March 2023) - Pasulo, L.; Barbui, A.; Camagni, S.; Leonardi, F.; D'Antiga, L.; Colledan, M.; Rambaldi, A.; Fagiuoli, S.
Abstract : Background: Primary sclerosing cholangitis (PSC) represents 5% of the indications for liver transplantation (LT). Recurrence of PSC (rPSC) is reported to occur in 8-27% and it has a great impact on both graft and patient survival. Methods: the clinical data of 35 patients with PSC who underwent LT at our center in the last 20 years were retrospectively evaluated. Twentyfive were male (71, 4%) with a history of IBD before OLT (67%). Tacrolimus+steroid was the most frequent immunosoppressive schedule (84.8%). Five patients (15.1%) underwent re-OLT (3 for rPSC, 2 for immunological damage). Graft and patient survival at 5 years were 73.6% and 88%. A female transplanted for the first time at the age of 17 years, redeveloped aggressive rPSC, with the need for a third LT. The time interval between second and third LT was much shorter than between the first and second LT (2015-2019-2021). In order to modulate the patient's immune reactivity, within 3 months from the 3rdLT, stem cell mobilization (cyclophosphamide+G-CSF) was performed, and CD34+ cells were selected: the patient eventually underwent autologous hematopoietic stem cell transplantation (aHSCT), preceded by a conditioning regimen (melphalan+rabbit antithymocyte globulin). In the immediate post-aHSCT, the patient experienced a E. Coli -related sepsis. The full immunosuppressive regimen was reintroduced 18days after aHSTC. Three and 14 months after aHSCT, she underwent follow-up liver biopsies which excluded rPSC and showed a picture of mild ectasia of centrolobular veins and pericentral sinusoids, associated with initial aspects of sclero-atrophy of the bile ducts, consistent with liver injury secondary to chemotherapy. Liver test were maintained normal. Conclusion: ReLT is the only treatment option for aggressive rPSC. Our patient succesfully underwent 3rd R-LT combined with aHSCT with no evidence of rPSC at over 14 months follow-up: this may represent a successful approach as a preemptive strategy in selected cases of reLT for rPSC.